2021
DOI: 10.1038/s41598-021-89036-3
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy does not decrease postoperative wound complications in patients undergoing mastectomy and flap fixation

Abstract: Patients and breast cancer surgeons are frequently confronted with wound complications after mastectomy. Negative pressure wound therapy (NPWT) is a promising technique for preventing wound complications after skin closure in elective surgery. However, a clinical study evaluating postoperative complications following the use of NPWT, focusing solely on closed incisions in patients undergoing mastectomy, has yet to be performed. Between June 2019 and February 2020, 50 consecutive patients underwent mastectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…A total of 1765 relevant studies were screened, of which 12 studies between 2014 and 2022, met the inclusion criteria, and were involved in the meta‐analysis. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Data obtained from these studies were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1765 relevant studies were screened, of which 12 studies between 2014 and 2022, met the inclusion criteria, and were involved in the meta‐analysis. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Data obtained from these studies were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The current meta‐analysis involved 2223 women with closed incisions in breast cancer surgery at the baseline of the studies; 964 of them were using the prophylactic application of negative pressure wound therapy, and 1259 were using standard dressings 18‐29 . With The prophylactic application of negative pressure wound therapy women had a significantly lower total wound problem, lower surgical site wound infection, lower wound dehiscence, and lower wound necrosis, in women with closed incisions in breast cancer surgery compared with standard dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VSD renders benefits to various types of surgeries. In breast surgery with easy recurrence and multiple complications, for example, the use of VSD can reduce seroma and its sequelae [22,23]. As an auxiliary treatment method for open wounds, VSD will apply controllable negative pressure to the wounds through various equipment and professional dressings, and transfer wound liquid to appropriate containers, which can create a wound environment conducive to healing by removing infected materials and exudates, reducing edema, and Evidence-Based Complementary and Alternative Medicine promoting perfusion and granulation [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…127,128 The NPWT controls the exudate by fluid removal and thus prevents infection and cross-contamination (Figure 4). 129 This method also reduces edema, stimulates angiogenesis, helps to maintain wound moisture, and finally promotes contraction of the wound edges. This technique has been used for the treatment of acute and chronic wounds, open wounds, burns, diabetic wounds and also venous and arterial wounds.…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%